Echocardiogram: The GPS to GPA’s Heart (Granulomatosis with Polyangiitis) - Manpreet K. Parmar; Mariam Alikhan; Vivien M. Hsu; Amanda Borham (Case Reports in Rheumatology)
Granulomatosis with polyangiitis (GPA) is a rare ANCA-associated necrotizing granulomatous vasculitis affecting small- to medium-sized vessels. Common manifestations of this disease process affect the ear, nose, throat, upper and lower airways, and kidneys. Cardiac involvement has been reported in 6–44% of patients, primarily as coronary arteritis and pericarditis. A majority of case reports of pericardial effusions in patients with GPA identify patients having constrictive pericarditis secondary to uremia. We are presenting a case of hemorrhagic pericarditis in a patient with GPA in which the underlying inflammatory vasculitis likely played the primary role in the patient’s presentation. Echocardiographic abnormalities have been found in 80% of patients with GPA. Given the high mortality from cardiac involvement in patients with GPA, screening echocardiograms for this patient population may serve as a helpful tool in gauging disease severity, thereby guiding therapy to prevent serious cardiac complications, such as cardiac tamponade as presented in this case report.